Assessing the effectiveness of embedding CFRP laminates in the near surface for structural strengthening - Ferreira, Débora (2006)
The Near Surface Mounted (NSM) technique is a recent strengthening strategy, using Fiber Reinforced Polymer (CFRP) systems, that is being developed to increase the bending and the shear resistance of structural elements. To assess the effectiveness of the NSM technique, an experimental program is carried out involving reinforced concrete (RC) columns, RC beams and masonry panels. In columns failing in bending the present work shows that CFRP failure strain can be attained using the NSM technique. In this study, beams of distinct steel reinforcement ratio failing in bending are strengthened with CFRP laminate strips in order to double their load carrying capacity. This goal was attained and maximum strain levels of about 90% of the CFRP failure strain were recorded. The effectiveness of externally bonded reinforcing (EBR) and NMS techniques are compared by carrying out three-point-bending tests with masonry panels failing in bending. The NMS technique has provided a higher increase of the load carrying capacity, deflection at panel failure and more homogeneous behavior during panel deformability. Performance of both EBR and NMS techniques are also compared for strengthening RC beams failing in shear. NMS is shown to be much more effective, not only in terms of the increase of the load carrying capacity and deformability at beam failure, but also with respect to the time consuming nature of the corresponding strengthening procedures.